Colloidosomes as Single Implantable Beads for the In Vivo Delivery of Hydrophobic Drugs. (9th April 2013) - Porta, Fabiola; Kros, Alexander
<x xml:space="preserve">Abstract</x> The synthesis of silica‐based colloidosomes with a polymer core obtained via inverse Pickering emulsification and their use as an implantable drug delivery system in zebrafish are described. Silica nanoparticles act as a stabilizer of a water‐in‐oil emulsion creating aqueous droplets with a silica shell. The core of the colloidosomes is polymerized resulting in tough particles. Colloidosomes loaded with model drugs show a release profile dependent on the porosity of the silica nanoparticles. Studying the effect of drugs on zebrafish development and tail regeneration is a new and emerging field in biomedical research. The in vivo delivery and bioactivity of retinoic acid from single implanted colloidosomes in partially amputated caudal fins are shown at the phenotype and genotype level. The colloidosomes are biocompatible since no signs of inflammation are observed. With these initial studies, the use of colloidosomes as single implantable beads is demonstrated for the local in vivo release of bioactive drugs. It is envisioned that these single particles can be applied for a broad range of hydrophobic drugs.